2017
DOI: 10.1155/2017/6747482
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantLactococcus lactisExpressing Haemagglutinin from a Polish Avian H5N1 Isolate and Its Immunological Effect in Preliminary Animal Trials

Abstract: Lactic acid bacteria (LAB) are Gram-positive, nonpathogenic microorganisms that are gaining much interest as antigen producers for development of live vaccine vectors. Heterologous proteins of different origin have been successfully expressed in various LAB species, including Lactococcus lactis. Recombinant L. lactis strains have been shown to induce specific local and systemic immune responses against various antigens. Our study aimed at constructing a L. lactis strain expressing haemagglutinin of a Polish av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…To date, a multitude of peptides, enzymes, and vaccines of clinical and biotechnological interest have been overexpressed using nisin, including the antibacterial protein lysostaphin (5), a hemagglutinin of the H5N1 influenza virus (28), and rotavirus VP6 protein (29), to name but a few. Though several improvements have been made to the NICE system, further improvements are possible.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a multitude of peptides, enzymes, and vaccines of clinical and biotechnological interest have been overexpressed using nisin, including the antibacterial protein lysostaphin (5), a hemagglutinin of the H5N1 influenza virus (28), and rotavirus VP6 protein (29), to name but a few. Though several improvements have been made to the NICE system, further improvements are possible.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a vaccine against bird flu is a good example of expressing a haemagglutinin antigen intracellularly, from a pSH71-based plasmid in L. lactis , instead of being secreted, to protect the antigen from the passage through the stomach. The H5 gene was cloned under the control of the nisin-controlled gene expression system in the pNZ8150 plasmid and the preliminary results showed that the oral delivery of live L. lactis cells producing H5 protein was able to elicit an immune response in chicken and mice [ 118 ]. A more recent example of a recombinant antigen being expressed in a soluble form in L. lactis cytoplasm was accomplished by Wang et al [ 105 ].…”
Section: Plasmid Vectors Available For Plasmid Dna and Recombinantmentioning
confidence: 99%
“…Additionally, L. lactis was used as expression host alternative to E. coli due to following advantageous properties i) generally recognized as safe (GRAS) microorganism ii) lack of outer membrane (iii) insignificant extracellular proteolysis activity (iv) free of endotoxins (v) no lipo-polysaccharide contamination (vii) accommodates cysteine-rich proteins (vii) accessibility of both inducible and constitutive genetic control systems (viii) able to express prone-toaggregate and/or difficult-to-purify proteins (ix) presentation to the host immune system in the context of micro-particles to avoids the immunotolerance, which is normally provoked by oral delivery of soluble antigens (x) exhibits similar codon bias to P. falciparum, which makes it efficient protein expression and secretion system to outer surface that could easily interact with host immune system [113,[141][142][143]. In recent years, several wet lab studies have confirmed the utilization of L. lactis as an expression host to produce properly folded, pure and stable chimeric and/or single antigenic proteins of many pathogens that elicited high levels of functional antibodies/cytokines including P. falciparum [144][145][146][147][148], Mycobacterium bovis [149], Mycobacterium tuberculosis [150], Helicobacter pylori [151], Polish avian H5H1 influenza [152], cancer [153] and Staphylococcus aureus [154]. Moreover, L. lactismediated delivery of DNA vaccines also lead to the expression of post-translationally modified antigens by host cells resulting in presentation of conformationally restricted epitopes to the immune system for induction of both cellular and humoral immune responses [112].…”
Section: Codon Optimization In Silico Cloning and Expression Of Pv1a And Pv3bmentioning
confidence: 99%